Comparison of four diagnostic indices for metabolic syndrome in a Northern Spanish population - Liliana Bilbie Lupchian; Bárbara Oliván-Blázquez; Edgar Peña-Galo; Marta Domínguez-García; María Antonia Sánchez-Calavera (PLoS ONE, 2026)
Cardiometabolic diseases are the leading cause of death worldwide, and early identification of individuals at risk is essential to reduce their burden. This study compared the performance of four diagnostic indices — the Visceral Adiposity Index (VAI), Body Mass Index (BMI), Waist Circumference (WC), and Atherogenic Index (AI) — in predicting Metabolic Syndrome (MetS) in a primary care population from northern Spain. A retrospective observational study was conducted using data from the CRONAP cohort (n = 3,107). Anthropometric and analytical parameters were analyzed using logistic regression and ROC curves. The VAI showed the highest predictive capacity for MetS (AUC = 0.779), followed by WC (0.756), BMI (0.730), and AI (0.665). In the MetS group, higher and statistically significant values were observed for glucose, glycated hemoglobin, triglycerides, blood pressure, BMI, and WC (p < 0.001), while HDL-cholesterol and glomerular filtration rate were lower. VAI outperformed the other indices in identifying MetS and may serve as a useful screening tool in primary care settings; however, as this is a retrospective, single-region study, further research is required to validate its diagnostic cut-off and generalizability to other populations.